The rebel in the arab world: toward democratization? (the case of tunisia and egypt) (2011)
The approach on this article provides evidence of how different is the reality in Tunes and Egypt compared to the one described by official and media discourses en France. This article addresses through a first approximation to the events, how the so called "revolutions" of 2011 en Tunes and Egypt has been understood,, in order to evaluate how deep is the current political change in both countries; which directions have been chosen and which obstacles may emerge . The concepts of revolution and democratic transition are critically analyzed having in mine the change of regime in these countries, using a framework that mixes the analysis of social mobilization and the political transitions. This article also emphasizes on the need to conduct a wider analysis taking into account the social and cultural change, particularly the link between democracy and Islam and the change on social norms. In order to understand the progressive loss of legitimacy of the political regime we also promote a sociological and detailed approach in a longer temporal perspective, in contrast with the mass media short term vision. Summarizing, this is an analysis of the conception itself of political change.